CONTACT FINITE ELEMENT ANALYSIS OF JOINT BEARING LAMINATED MEMBRANE COUPLING UNDER COMPOSITE LOADING - SHENTU LiuFang; SUN ChengLong; ZHAO QingJia; ZHANG Yan (Jixie qiangdu, 2016)
In order to explore the stress characteristic of flexible components of the laminated membrane coupling,according to the contact finite element model of laminated group,the stress distributing graphs under the comprehensive load are obtained. Based on the finite element analysis software ANSYS,the geometric model of laminated group is provided,some contacts between the diaphragms are added and methods of applying different loads are proposed. Effects of number of diaphragm on laminated stress are analyzed,and distribution curve of maximum equivalent stress and contact stress on laminated group which from four layers to nine layers are obtained. With laminated group which have nine layers as an example,distribution curves of equivalent stress and contact stress due to different torques,different axial displacements and different angular displacements were obtained. Study shows that Mutative angular displacement is the key effect of laminated stress among various kinds of loading,and the breaking point first occurred around the washer on the lateral diaphragms under the action of composite loading. The compensation capacity,use efficiency of the laminated membrane coupling with joint bearing are greater than the laminated membrane coupling without joint bearing under composite loading.